ELABELA antagonizes intrarenal renin-angiotensin system to lower blood pressure and protects against renal injury - Xu, Chuanming (Am J Physiol Renal Physiol, 2020)
Emerging evidence has demonstrated that (pro)renin receptor (PRR)-mediated activation of intrarenal renin-angiotensin system (RAS) plays an essential role in renal handling of Na(+) and water balance and blood pressure. The present study tested the possibility that the intrarenal RAS served as a molecular target for the protective action of ELABELA (ELA), a novel endogenous ligand of apelin receptor, in the distal nephron. By RNAscope and immunofluorescence, mRNA and protein expression of endogenous ELA was consistently localized to the collecting duct (CD). Apelin was also found in the medullary CDs as assessed by immunofluorescence. In cultured CD-derived M1 cells, exogenous ELA induced parallel decreases of full-length PRR (fPRR), soluble PRR (sPRR), and prorenin/renin protein expression as assessed by immunoblotting and medium sPRR and prorenin/renin levels by ELISA, all of which were reversed by 8-bromoadenosine 3′,5′-cyclic monophosphate. Conversely, deletion of PRR in the CD or nephron in mice elevated Apela and Apln mRNA levels as well as urinary ELA and apelin excretion, supporting the antagonistic relationship between the two systems. Administration of exogenous ELA-32 infusion (1.5 mg·kg(−1)·day(−1), minipump) to high salt (HS)-loaded Dahl salt-sensitive (SS) rats significantly lowered mean arterial pressure, systolic blood pressure, diastolic blood pressure, and albuminuria, accompanied with a reduction of urinary sPRR, angiotensin II, and prorenin/renin excretion. HS upregulated renal medullary protein expression of fPRR, sPRR, prorenin, and renin in Dahl SS rats, all of which were significantly blunted by exogenous ELA-32 infusion. Additionally, HS-induced upregulation of inflammatory cytokines (IL-1β, IL-2, IL-6, IL-17A, IFN-γ, VCAM-1, ICAM-1, and MCP-1), fibrosis markers (TGF-β(1), FN, Col1A1, PAI-1, and TIMP-1), and kidney injury markers (NGAL, Kim-1, albuminuria, and urinary NGAL excretion) were markedly blocked by exogenous ELA infusion. Together, these results support the antagonistic interaction between ELA and intrarenal RAS in the distal nephron that appears to exert a major impact on blood pressure regulation.